Subclasses of analytic functions defined by new generalised derivative operator - El-Yagubi, Entisar; Maslina Darus (Penerbit Universiti Kebangsaan Malaysia, 2013)
A new generalised derivative operator 12,,,nmDbλλ is introduced. This operator generalised some well-known operators studied earlier. New subclasses of analytic functions in the open unit disc which are defined using generalised derivative operator are introduced. Inclusion theorems are investigated. Furthermore, generalised Bernardi-Libera-Livington integral operator is shown to be preserved for these classes.